Mitochondrial Fatty Acid Beta-Oxidation Disorders in Children: Literature Review - Natalia V. Zhurkova; Nato V. Vashakmadze; Andrey N. Surkov; Olga Ya. Smirnova; Natalia S. Sergienko; Natallia G. Ovsyanik; Lilia R. Selimzyanova (Вопросы современной педиатрии, 2023)
Congenital mitochondrial fatty acid beta-oxidation disorders are a heterogeneous group of metabolic disorders characterized by impaired fatty acid metabolism in mitochondria. It results in central nervous system, skeletal muscle, cardiovascular system, and liver damage, as well as the development of nonketotic hypoglycemia. The age of disease manifestation and its severity range from severe (neonatal) to milder myopathic (adult) forms. The extension of the mass screening program in Russian Federation allows to detect these diseases during the first weeks of life. The availability of effective therapy for mitochondrial fatty acid beta-oxidation disorders, especially during early diagnosis, enables timely stabilization of the patient's condition and prevention of severe complications. Awareness of pediatricians, neonatologists, neurologists, and cardiologists about such diseases is the urgent task of modern pediatrics.